Parents' experiences of life after medicalised conception: a thematic meta-synthesis of the qualitative literature - Z. Foyston; L. Higgins; D. M. Smith; A. Wittkowski (BMC, 2023)
Abstract Background Medicalised Conception (MAC) assists many couples to achieve pregnancy worldwide. As the impact of MAC has been linked to increased pregnancy-specific anxiety and parenting difficulties, this review aimed to explore parental experiences of pregnancy and early parenting following MAC, identifying parents' psychological, social and health needs. Method Five databases were searched systematically from inception to March 2023. Identified articles were screened for eligibility against the inclusion criteria and the results were analysed using thematic synthesis. The Critical Appraisal Skills checklist was employed to appraise methodological quality. Results Twenty qualitative studies, drawing on a total of 19 participant samples, were included in this review, most with samples with history of subfertility. The findings were synthesised into three main themes (consisting of seven subthemes): 1) The vulnerable parent: fear, doubt, uncertainty, 2) the stark realisation of the parental dream, 3) psychosocial needs and support. Parents lacked a sense of safety during pregnancy and reported acting protectively both antenatally and postnatally. Furthermore, their identity transition was complex and non-linear, influenced by sociocultural context. Conclusions Considerable unmet psychosocial needs were identified including the potential for anxiety in pregnancy, the possibility of feeling excluded and marginalised, and a reluctance to share distress and experiences with healthcare professionals. These findings suggest a need for consistent, holistic care, integrating psychological services.